The Relationship between Self-Management and Quality of Life in the Elderly with Hypertension in the Working Area of the Limboto Health Center - Amelisa Pakaya; Nanang R. Paramata; Andi Mursyidah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to determine the relationship between self-management and the quality of life of the elderly with hypertension in the working area of the Limboto Health Center. This research is included in quantitative research using a cross-sectional approach. Self-management of elderly people with hypertension in the Limboto Health Center Working Area is in the good category, namely as many as 43 respondents (65.2%), enough as many as 21 respondents (31.8%) and 2 respondents (3.0%) are in the poor category. The quality of life of elderly people with hypertension in the Limboto Health Center Working Area was in the good category as many as 24 respondents (36.4%), while as many as 20 respondents (30.3%), very good as many as 19 respondents (28.8%) and 3 respondents (4.5%) were in the bad category. There is a relationship between self-management and the quality of life of elderly people with hypertension in the Limboto Health Center Working Area. Significance value (p-value) = 0.000 (<0.05) which means that there is a significant relationship between self-management and the quality of life of the elderly with hypertension. The correlation coefficient value of 0.717 indicates the strength of the relationship with the direction of a positive relationship, which means that the increase in the respondents' self-management ability contributes to an improvement in quality of life.